2004
DOI: 10.4049/jimmunol.173.6.4130
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Thrombospondin-1 Is Necessary for the Vitamin D-Binding Protein (Gc-Globulin) to Function as a Chemotactic Cofactor for C5a

Abstract: The chemotactic activity of C5a and C5a des Arg can be enhanced significantly by the vitamin D-binding protein (DBP), also known as Gc-globulin. DBP is a multifunctional 56-kDa plasma protein that binds and transports several diverse ligands. The objective of this study was to investigate the mechanisms by which DBP functions as a chemotactic cofactor for C5a using neutrophils and U937 cells transfected with the C5aR (U937-C5aR cells). The results demonstrate that U937-C5aR cells show C5a chemotactic enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Recently, we have speculated that formation of a DBP binding site complex is a dynamic, multistep, and transient process involving perhaps several distinct cell surface macromolecules (15). However, the precise components that form the binding site complex as well as the mechanism(s) by which DBP enhances chemotaxis to the C5-derived peptides are not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have speculated that formation of a DBP binding site complex is a dynamic, multistep, and transient process involving perhaps several distinct cell surface macromolecules (15). However, the precise components that form the binding site complex as well as the mechanism(s) by which DBP enhances chemotaxis to the C5-derived peptides are not known.…”
mentioning
confidence: 99%
“…The DBP binding site complex has been inferred by functional, structural, and kinetic cell binding studies (10,(13)(14)(15). Recently, we have speculated that formation of a DBP binding site complex is a dynamic, multistep, and transient process involving perhaps several distinct cell surface macromolecules (15).…”
mentioning
confidence: 99%
“…However, very little mechanistic information is available concerning how DBP enhances chemotaxis to the C5 derived peptides. Several studies from our laboratory have demonstrated that the binding of DBP to the neutrophil plasma membrane, and subsequent protease-mediated shedding of the binding site, are essential for the chemotaxis enhancement of C5a (DiMartino and Kew, 1999;DiMartino et al, 2001;Kew et al, 1995a;Kew et al, 1995b) More recently, we have demonstrated that DBP requires platelet-derived thrombospondin-1 for maximal cochemotactic activity (Trujillo and Kew, 2004). In addition, cell surface CD44 and annexin A2 are part of a DBP binding site complex and mediate the C5a chemotactic cofactor function of DBP (McVoy and Kew, 2005).…”
Section: Discussionmentioning
confidence: 81%
“…2) but obviously does not. Moreover, the chemotactic activity in complement-activated serum is DBP-dependent because immunodepletion of DBP from activated serum reduces the chemotactic activity by almost 75% without altering the levels of C5a (Kew and Webster, 1988;Trujillo and Kew, 2004). This apparent paradox may be explained by how and when 1,25(OH) 2 D 3 interacts with neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation